Treatment of pemphigus and other neglected skin conditions with PC111, a human anti-Fas Ligand monoclonal antibody: a potential disease modifier - Roberta Lotti; Antonino Amato; Brydon Bennett; Tommaso Zanocco-Marani; Alessandra Marconi; Carlo Pincelli (Journal of Dermatological Treatment, 2025)
Background Pemphigus vulgaris (PV) is a chronic autoimmune blistering disease with high morbidity and mortality, treated mainly with long-term immunosuppressants. Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis (SJS/TEN) is an acute, life-threatening drug reaction with severe skin and mucosal involvement. No approved therapies currently exist for SJS/TEN.Aim To demonstrate that the soluble form of Fas ligand (sFasL) is a relevant therapeutic target in both PV and SJS/TEN, and to provide evidence that PC111, a fully human monoclonal antibody against sFasL, is effective in both conditions.Evidence review In PV, autoantibodies (PVIgG) target desmogleins, leading to blistering via signaling cascades. sFasL, released upon PVIgG binding, contributes to this process by promoting desmoglein degradation and acantholysis. In SJS/TEN, elevated sFasL induces keratinocyte apoptosis, contributing to epidermal detachment.Findings PC111 blocks acantholysis and blister formation in PV through a local, rapid mechanism, downstream of the immune system, thus differentiating from the currently used immunosuppressive treatments. In SJS/TEN, PC111 prevents keratinocyte apoptosis induced by patient serum and improves ocular symptoms in a mouse model. Its fast action suggests potential for early intervention to halt disease progression.Conclusions PC111 may act as a disease-modifying agent, promoting long-term remission in PV and preventing progression in early-stage SJS/TEN.